2000
DOI: 10.1002/1097-0215(20001001)88:1<77::aid-ijc12>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 protein expression and gene polymorphism in colorectal cancer

Abstract: Cyclin D1 is a key cell cycle regulatory protein, the expression and subcellular localization of which is often altered in human tumor cells. A common A/G single nucleotide polymorphism (A870G) in exon 4 of the cyclin D1 gene, CCND1, is associated with the presence of 2 distinct mRNA transcripts for this G1/S regulatory protein, and CCND1 genotype has been related to prognosis in lung cancer and head and neck carcinoma. We have investigated both the expression of cyclin D1 protein and the CCND1 A870G polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
87
6
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 22 publications
11
87
6
3
Order By: Relevance
“…Specifically, we showed a trend for increased p21 Cip1 levels with tumour progression and that p21 Cip1 is potentially elevated in tumours with high nuclear cyclin D1 ( Figure 5A and C). These observations are consistent with observations in other tumour types (McKay et al, 2000;Holland et al, 2001;Tut et al, 2001) and support its role in promoting cyclin D1/CDK4 activity. Second, we showed that p21 Cip1 levels correlate with proliferation ( Figure 5B), thus confirming other reports (Ljung et al, 1997;Baretton et al, 1999;Osman et al, 1999;Fizazi et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, we showed a trend for increased p21 Cip1 levels with tumour progression and that p21 Cip1 is potentially elevated in tumours with high nuclear cyclin D1 ( Figure 5A and C). These observations are consistent with observations in other tumour types (McKay et al, 2000;Holland et al, 2001;Tut et al, 2001) and support its role in promoting cyclin D1/CDK4 activity. Second, we showed that p21 Cip1 levels correlate with proliferation ( Figure 5B), thus confirming other reports (Ljung et al, 1997;Baretton et al, 1999;Osman et al, 1999;Fizazi et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…This observation suggests that restriction of cyclin D1 to the cytoplasm may allow suppression of cellular proliferation but requires a more rigorous investigation. Interestingly, a number of colorectal cancer studies have observed cytoplasmic cyclin D1 in tumour specimens (Palmqvist et al, 1998;Handa et al, 1999;McKay et al, 2000;Holland et al, 2001;Khor et al, 2006;Kuramochi et al, 2006) and at least one of these studies has reported that increased cytoplasmic cyclin D1 correlated with low proliferation (Palmqvist et al, 1998). This result is similar to our analyses ( Figure 4C), wherein tumours with predominately cytoplasmic cyclin D1 showed a significantly lower proliferative index.…”
Section: Discussionsupporting
confidence: 90%
“…Although the CCND1 polymorphism was not associated with the onset of colorectal cancer in a small population, 29 Zheng et al 30 reported that the AA genotype was associated with an increased risk of colorectal cancer at a younger age. Furthermore, patients with at least 1 A allele developed colorectal cancer at an average of 11 years earlier than those without the A allele, suggesting a dominant effect of this allele on tumor onset in hereditary nonpolyposis colorectal cancer.…”
Section: Discussionmentioning
confidence: 93%
“…1 Increased cyclin D1 expression has been reported as an early event in colorectal tumorigenesis 2 and has been observed in other cancer types, including prostate, breast, lung and endometrial carcinomas. 3,4 Prior work has shown, however, that CCND1 is not essential for the development of colorectal cancer, although it may act as a modifier of disease severity. 5 Most association studies of CCND1 have so far focused on the common and functionally significant G870A (P241P, rs9344) polymorphism, which affects splicing by eliminating a donor site at the end of exon 4.…”
Section: Introductionmentioning
confidence: 99%